Vertical annular gas–liquid two-phase flow in large diameter pipes - Aliyu, Aliyu M. (Cranfield University, 2015)
Gas–liquid annular two phase flow in pipes is important in the oil and gas, nuclear and the process industries. It has been identified as one of the most frequently encountered flow regimes and many models (empirical and theoretical) for the film flow and droplet behaviour for example have been developed since the 1950s. However, the behaviour in large pipes (those with diameter greater than 100 mm) has not been fully explored. As a result, the two- phase flow characteristics, data, and models specifically for such pipes are scarce or non-existent such that those from smaller pipes are extrapolated for use in design and operation. Many authors have cautioned against this approach since multiphase pipe flow behaviour is different between small and large pipes. For instance the typical slug flows seem not to occur in vertical upwards flows when the pipe diameter exceeds 100 mm. It is therefore imperative that theoretical models and empirical correlations for such large diameter pipes are specifically developed. ...[cont.]
Keywords: Adiabatic two-phase flow; Entrained droplet fraction; Falling films; Interfacial friction factor; Multiphase flow; Pressure gradient